AB0636 Ustekinumab as a Therapeutic Option for Takayasu Arteritis –from Genetic Findings to Clinical Application-. (9th June 2015) - Terao, C.; Yoshifuji, H.; Yukawa, N.; Nakajima, T.; Matsuda, F.; Mimori, T.
Abstract : Background: Takayasu arteritis (TAK) is a systemic vasculitis affecting aorta and its large branches. While patients with TAK respond to glucocorticoids and immunosuppressants, they often flare up. A novel therapeutic option based on pathophysiological findings of TAK is desired. We recently identified IL12B as a susceptibility gene through genome-wide association study. Since ustekinumab, monoclonal antibody to IL-12/23p40 encoded by IL12B, is an effective treatment for Crohn's disease and psoriasis both of which share IL12B as a susceptibility gene, we hypothesized that ustekinumab would be effective to patients with TAK. Objectives: To perform a pilot clinical trial where we used ustekinumab to assess its safety and efficacy for patients with TAK. Methods: We administered 40mg of ustekinumab at day 0 and 28 to a total of three patients with refractory TAK. All patients were evaluated for disease activity by MRI at baseline and on day 84. Results: All of the three patients showed enhancement in vascular walls at baseline.Two patients showed acute inflammatory responses at registry and the other suffered from severe head and neck pain and general fatigue. Both patients with acute inflammatory responses showed decreased levels of C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) (p<0.05). The other patient showed remarkable relief from pain and general fatigue. No side effects were observed. In spite of response to ustekinumab, we did not observe any change in vascular wall enhancement on day 84. All the patients remained in good status at least on day 100. Conclusions: Ustekinumab would be a safe and effective treatment option for TAK warranted by the genetic association. A large-scale clinical study is necessary to accumulate evidence of its usefulness. References: Terao C, Yoshifuji H, Mimori T. Recent advances in Takayasu arteritis. Int. J. Rheum. Dis. 2014;17:238-47. Terao C, Yoshifuji H, Kimura A, et al. Two susceptibility loci to Takayasu arteritis reveal a synergistic role of the IL12B and HLA-B regions in a Japanese population. Am. J. Hum. Genet. 2013;93:289-97. Saruhan-Direskeneli G, Hughes T, Aksu K, et al. Identification of Multiple Genetic Susceptibility Loci in Takayasu Arteritis. Am. J. Hum. Genet. 2013. Yeilding N, Szapary P, Brodmerkel C, et al. Development of the IL-12/23 antagonist ustekinumab in psoriasis: past, present, and future perspectives–an update. Ann. N. Y. Acad. Sci. 2012;1263:1-12. Sandborn WJ, Gasink C, Gao LL, et al. Ustekinumab induction and maintenance therapy in refractory Crohn's disease. N. Engl. J. Med. 2012;367:1519-28. Cargill M, Schrodi SJ, Chang M, et al. A large-scale genetic association study confirms IL12B and leads to the identification of IL23R as psoriasis-risk genes. Am. J. Hum. Genet. 2007;80:273-90. Acknowledgements: We would like to thank members of the Department of Rheumatology and Clinical Immunology in Kyoto University for their support. We also thank Dr. Hirofumi Makino in Okayama University as well as members of the working group of vasculitis for helping us to obtain a grant for this project. This work was supported by research grants from the Japan Intractable Diseases Research Foundation. Disclosure of Interest: None declared